Kesiapan Lingkungan KKESIAPAN LINGKUNGAN KERJA PERAWAT DALAM PELAKSANAAN RESUSITASI JANTUNG PARU DI INSTALASI RAWAT INAP RUMAH SAKIT X: Readiness of the Nurse's Work Environment in the Implementation of Cardiopulmonary Resuscitation in the Inpatient Installation of Hospital X - Elizabeth Ari Setyarini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
The nursing work preparation used for cardiopulmonary resuscitation as a treatment of cardiac arrest and breathing conditions divided into physical and non-physical environments. The total of cardiac arrest cases in X Hospital from January-December 2016 was 402 cases. The success of cardiopulmonary resuscitation in hospitals is influenced by working conditions. Preliminary study results obtained some incomplete tools in accordance with the Standard Operational Procedure (SPO), the information of difficulty of mobilization during CPR in a certain room and unclear instructions from the CPR leader. The objectives of the research were to identify the nursing work preparation cardiopulmonary resuscitation of the X hospital. The study method was a quantitative used cross-sectional approach, with a total sampling subject. The results showed that almost all (89,8%) of a physical preparation at the In-patient Room of X Hospital fulfilled in accordance with the procedure of X Hospital. Some respondents (58,3%) nurses have good non-physical preparation at the In-patient room of X Hospital. Researchers suggest checking and managing emergency trolleys, improving organizational communication.